"In the Margins of Europe": Cypriot Nationalism, Liminality, and the Moral Economy of the Financial Crisis. Issue 1 (2nd January 2017) - Argyrou, Vassos
Abstract : This article argues that Greek Cypriot nationalism has been in large part motivated by the misconceived idea of Cyprus becoming a modern, European society. Although Cyprus joined the European Union in 2004, the perception of it by the European north as a culturally marginal Mediterranean society had not changed. This was amply demonstrated in 2013 when Cyprus applied to the EU for urgent financial assistance. It was forced to capitalize its banks through their customers' savings and, although this and other "corrective" measures were couched in seemingly rational economic terms, they were unmistakably a punishment and a civilizational lesson.